KOREAN BOY GROUP FANS IN INDONESIA: SNA STUDY #WE LOVE YOU JUNGKOOK VS #FULL ALBUM - Tri Nada Nisrina; Osly Usman (Journal of Economics, Business, and Government Challenges, 2021)
This study examines the role of #WE LOVE YOU JUNGKOOK and #FULL ALBUM on Twitter in shaping digital opinion support mobilization, measuring the comparison of networks, actors between hashtags, and digital opinion. The theory used is the Digital Movement of Opinion by looking at the level of actors and the system. The research method is a quantitative combination for communication networks with a sample of 5,000 tweet data: 2500 #WE LOVE YOU JUNGKOOK tweet data with 2964 actors, 1673 relationships and 2500 #FULL ALBUM tweet data with 2027 actors and 1478 relationships using netlytic with qualitative data to analyze the text study and explain social networks. The results showed that #FULL ALBUM is more capable of creating mobilization than #WE LOVE YOU JUNGKOOK.